Real-world tafamidis experience in hereditary transthyretin amyloidosis with peripheral neuropathy in Brazil - Luiz Felipe Pinto; Marcus V. Pinto; Paula Accioli; Gabriela Amorim; Renata Gervais de Santa Rosa; Moises Dias; Mariana Guedes; Carlos P. Gomez; Roberto C. Pedrosa; Marcia Waddington-Cruz (Arquivos de Neuro-Psiquiatria)
Background Tafamidis is a kinetic stabilizer that binds to the transthyretin (TTR) gene, inhibiting its dissociation. It is the only disease-modifying treatment for hereditary TTR amyloidosis with peripheral neuropathy (ATTRv-PN) available in the National Therapeutic Form (Formulário Terapêutico Nacional, FTN, in Portuguese) of the Brazilian Unified Health System (Sistema Único de Saúde, SUS, in Portuguese).